Nordeste Brasileiro multifacetado: do sertão bucólico aos ventos que tocam o litoral - Rodrigues, Frederico do Nascimento (2021)
This research is based on a historical context, from an analysis that takes place in time-space, through progressive-regressive movements, representative of a diachronic research. It investigates historical developments that invoke/consolidate founding images of the colonial Northeast, such as cattle raising/cotton farming in the bucolic sertão and sugar production in the zona da mata, which we call the region's beginnings. Today, one can glimpse a multifaceted, plural, diverse, virtuous and "modern" Northeast based on agribusiness, producer of fruits and grains, reproducing the first imagery in contemporary times, and the sun and sea tourism, representative of the second. These activities, roughly speaking, dynamize and modify the northeastern landscapes, activities that encompass national and international scale, generating flows of commodities and people, respectively. In this scenario, there is a new variable that enters the Northeastern coastal ambiences, which adheres to new perspectives, becoming visible not only for the tourist activity, but also for the production of wind energy that dot the Brazilian coast, especially the Northeastern one, which accounts for 86% of the wind energy produced in the country, on specific days, about 90% of the energy consumed in the region comes from the trade winds. Of the 695 wind farms installed on national territory 599 are located in the Northeast. In this perspective, the thesis notes that today we are witnessing the consolidation of a third imagery, which is defined as the "Northeast that discovered the winds", and that begins to invest heavily in the production of "sustainable" energy from the winds that touch the coast and the backlands, thus spreading a virtual and positive image of the region merged with agribusiness and coastal tourism. A small number of privileged entrepreneurs working in the agricultural, tourism, and/or wind energy sectors obscure the negative images of the past of a poor, semi-arid, and hungry Northeast. The image of a region of possibilities is created to attract national/international investments, contributing to the conception of the modern and attractive. The research focuses on a qualitative investigation, with quantitative measurements in parallel, presenting itself as an exploratory study where methodological procedures such as observation, interviews, documentary research, bibliographic and secondary data survey, preparation of charts, graphs, cartographic production, capturing primary data through the application of electronic questionnaires, these are some steps of the research to achieve the proposed objectives.